Malignant Hyperthermia: A Case Report - Sousa, Mara Diva; Peixoto, Rita; Peixoto, Rita; Silva, Rui; Guedes, Luísa (Journal of the Portuguese Society of Anesthesiology, 2020)
Malignant hyperthermia (MH) is a very rare inherited disorder. The incidence of MH is 1:100 000 although the prevalence of susceptibility to MH is estimated at 1:2000 to 1:3000. MH has a mortality rate of 9.5%. MH is an autosomal dominant disorder and three genes account for the genetic basis of 70% of the patients - RYR1, CACNA1S and STAC3. MH is characterized by an increased body metabolism with hyperthermia, increased carbon dioxide production, skeletal muscle rigidity along with rhabdomyolysis, hyperkalaemia and acidosis with hyperlactacidaemia. These occur when a MH-susceptible individual is exposed to some known triggers such potent volatile anaesthetics and succinylcholine. We present a case report of MH in 22-year-old male ASA II, without any personal or familial MH susceptibility known, admitted to elective dental extraction who suffered a MH crisis. The patient was treated for MH and demonstrated a significant clinical improvement with the administration of dantrolene.